Performance analysis of a prototype small scale electricity-producing biomass cooking stove - O'Shaughnessy, Seamus; Robinson, Anthony (My University, 2015)
An electrical generator has been integrated with a locally produced, biomass-fed clay cooking stove in rural Malawi. The generator produces small amounts of electricity based on the thermoelectric effect. Five demonstrator stoves were deployed into a rural community in the Balaka district for up to 6 months. This study investigates the power generation performance of the devices over the first 80 days of the field trial. It was determined that the users were able to charge mobile phones, lights and radios from the generator stoves. The power generating performance of the stoves deteriorated slightly over the 80 day period. The was due to the effects of thermal cycling on the generator system as a whole which caused eventual drying out of the thermal paste and a loosening of the clamping nuts which reduces clamping pressure and power output. One stove failed due to a mechanical problem. It was found that the power produced significantly exceeded the power consumed in most cases, which indicates an over-supply. It appears that 3 W h is sufficient to meet the average daily electrical power requirements for the participants in this study. The data obtained from the field trial has been used to inform a redesign of the device for a second field trial.
PUBLISHED
Keywords: Malawi; Phone charging; Electricity generation; Thermoelectric; Cooking stove; Biomass; International Development; International Integration; Smart & Sustainable Planet; Mechanical Engineering; Renewable energies; Thermoelectricity